New vaccine strategies against enterotoxigenic Escherichia coli: I: DNA vaccines against the CFA/I fimbrial adhesin - Alves,A.M.B. (1999)
Stimulation of the mammalian immune system by administration of plasmid DNA has been shown to be an important approach for vaccine development against several pathogens. In the present study we investigated the use of DNA vaccines to induce immune responses against an enteric bacterial pathogen, enterotoxigenic Escherichia coli (ETEC). Three plasmid vectors encoding colonization factor antigen I (CFA/I), an ETEC fimbrial adhesin, were constructed. Eukaryotic cells transfected with each of these plasmids expressed the heterologous antigen in different compartments: bound to the cytoplasmic membrane (pRECFA), accumulated in the cytoplasm (pPolyCFA) or secreted to the outside medium (pBLCFA). BALB/c mice were intramuscularly (im) inoculated with purified plasmid DNA and the systemic, cellular and secreted CFA/I-specific immune responses were analyzed. The results showed that all three DNA vaccine formulations could elicit CFA/I-specific immune responses. Moreover, cellular location of the plasmid-encoded CFA/I seems to have an important role in the induced immune response. Taken together, these results indicate that DNA vaccines also represent a promising approach against enteric bacterial pathogens.